Design and Manufacturing of Pneumatic Switch from Available Cheap Materials (Journal of University of Babylon for Engineering Sciences, 2021)
This work is to build pneumatic switch, especially depending on air or gas flow, from a very cheap parts available as a waste material in reforming shops and small factories. Also, this pneumatic switch is carefully designed in a way that any primitive technician or smith can build it.  At the beginning, the parts of switch are designed using Catia Software and some parts are imported to ANSYS WORKBENCH 2020 R2 software to check the mechanical stresses associated with loads. Then, theoretical computations are made where the angular displacement is calculated, based on equations solved by MATLAB software, when the switch faces flow air stream for different speed magnitudes. After that, a real switch is built and be subjected to those same different air speed magnitudes used in theoretical computations. Then, comparison between the two results is made, which show there is a relatively slide difference in angular displacement readings as well as the switch has enough strength to resist the loads based on what is computed in theoretical side and what is noted in practice.